PENGARUH BAURAN PEMASARAN TERHADAP KEPUTUSAN PEMBELIAN ULANG PAKET NETFLIX - Hendrawan, Maychel Ferry (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2022)
Marketing mix is one of the instruments for conducting marketing activities as it can be a key factor for increasing repeat purchase value. Appropriate and effective marketing-mix activities can make consumers repeat their purchases. The objective of this research is to identify the effects of product, promotion, price, and place on the repeat purchase of Netflix. This digital streaming service was first made available in Indonesia in January 2016 and has attracted people’s interest since then by offering original contents. The respondents of this quantitative research are 100 Netflix users who have made repeat purchase. Using descriptive analysis and multiple linear regression, this study finds that product has a significant effect on the repeat purchase, while promotion, price, and place do not. The appropriate and effective marketing mix to be applied to stimulate repeat purchase for Netflix package is product improvements in terms of quality, display, and variants.